Bractwa religijne w diecezji lubelskiej w XIX wieku – stan liczbowy - Partyka, Wiesław (Archiwa, Biblioteki i Muzea Kościelne, 2014)
The brotherhood movement was born in the Church in the fourth century. Brotherhoods usually operated in churches and monasteries, and their aim was to strengthen the piety of the faithful through the implementation of the objectives of charitable and social activities, as well as activities connected with worship. In Poland, religious brotherhoods appeared in the thirteenth century and developed over the centuries. They fl ourished in the seventeenth and eighteenth century and were introduced into the majority of parishes. At the end of the fourteenth century they appeared in the region of Lublin. In the period before the partitions there were 174 brotherhoods in that region. With the collapse of the Polish State religious brotherhoods also experienced a serious crisis. The Diocese of Lublin was founded in 1805. Under the new organizational structures brotherhoods continued to operate and pursue their goals. Despite a series of reprisals from the partitioners, which wanted to tightly control and even restrict the activity of brotherhoods, they effectively coped with those diffi culties opposing the secularization of society. On the basis of the records of canonical visitation of the nineteenth century and the two registrations of brotherhoods in that period, it was possible to establish that in the nineteenth century in the Diocese of Lublin there were199 brotherhoods. The vast majority of brotherhoods were Marian ones – 124, of which 91 Rosary ones, 24 scapular ones and 9 others. Among other fraternities quite numerously represented were the ones dedicated to the Holy Trinity (24), St. Anna (15), Mercy (12). The number of such fraternities as Corpus Christi (3), St. Tekla (3), St. John of Nepomuk (3) Literary (2), St. Anthony (2) and Heart of Jesus (2) was small. There was also one brotherhood of Guardian Angels, one of the Holy Name of Jesus, Lovers of Crucifi ed Jesus, Merciful Jesus (dying), St. Cross, St. Mary Magdalene, St. Barbara, St. Yvonne and St. Francis of Assisi’s belt. Some of them disappeared at the beginning of the nineteenth century, some operated continuously for a long time and others came into existence in the period under discussion. It is hoped that the issue concerning the functioning of religious brotherhoods in the nineteenth century will soon be more detailed studied, as in the case of the fraternities operating in the period before the Partitions of Poland. It is essential to better understand not only the functioning of the brotherhoods in an entirely new political situation of the Polish Church but also their impact on moral and religious renewal, and perhaps on the increase in the patriotic sentiments of wider social groups.